Outer Space: is it a global common? - Kaul, Ranjana (Frontiers in Space Technologies, 2024)
This review examines critical questions related to whether the outer space is a global common; it also addresses the challenge of achieving balance between the outer space treaty (OST) mandate of compliance with the common interest principle and requirement of providing an environment for the success of commercial lunar enterprises while simultaneously mitigating the possibility of conflict on the Moon.